Molecular Structure Considerations for the Possibility of Sequence-Dependent DNA Resonances - Ivan Savelev; Alexandre A. Vetcher; Nelli Zyryanova; Richard A. Miller; Max Myakishev-Rempel (Proceedings)
For years, the mechanisms of non-chemical and non-contact communication between cells and organisms have not been studied to the same extent as those associated with the chemical mediators [...]